THE ESTROGEN-MECHANISM OF NEUROPROTECTION - Petrovska, Sunchica; Dejanova, Beti; Mancevska, Sanja; Gligorovska, Jasmina Pluncevikj (Journal of Morphological Sciences; Vol 5 No 3 (2022): JMS, 2022)
Estrogen is an important steroid hormone signal that regulates multiple tissues and functions in the body.The brain is an important target organ for estrogen. In addition to direct effects, estrogen influences brain function through effects on the vasculature and the immune system. Estrogen influences several neurotransmitter systems, including acetylcholine, serotonin, noradrenalin, and glutamate. There are complex mechanisms that underlie estrogen neuroprotective and neurotrophic actions (genomic, non-genomic kinase signalic pathways and membrane estrogen receptors pathways). Estradiol induces gene transcription and rapid membrane signaling mediated by estrogen receptor alpha (ERÎ±), estrogen receptor-beta (ERÎ²), and a recently characterized G-protein coupled estrogen receptor, each with distinct distributions and ability to influence estradiol-dependent signaling.Vector-mediated expression of estrogen receptors in the hippocampus provides an innovative research approach and suggests that memory depends on the relative expression of ERÎ± and ERÎ² interacting with estradiol levels.The potential role of estrogen as a neuroprotective factor and a multicellular mode of estrogen action in the regulation of neuronal survival and neurotrophism is discussed, as are potential future directions for the field. Key words: estrogen; estrogen  receptors; steroid hormone;  neuroprotection ;